Open Source License Proliferation: Helpful Diversity or Hopeless Confusion? - Robert W. Gomulkiewicz (Washington University Journal of Law & Policy, 2009)
This Article analyzes the license proliferation issue. In general, it examines whether the growing number of FOSS licenses represents hopeless confusion or, instead, helpful diversity. In particular, it discusses why proliferation occurs and the pros and cons of multiple licenses.
Keywords: Open source software; Software license agreements; Software licensing